2023
DOI: 10.1097/phm.0000000000002231
|View full text |Cite
|
Sign up to set email alerts
|

Frailty education: promoting geriatric competencies among Physical Medicine and Rehabilitation residents

Abstract: Frailty, a geriatric syndrome of growing importance in recent years, has been shown to be associated with increased risk of disability and adverse health and socioeconomic outcomes. Therefore, there is a need for new educational strategies for physical medicine and rehabilitation residents to promote greater geriatric competencies, with a focus on developing customized evaluation and management plans. With this article, the aim is offering a quick reference tool summarizing the latest evidence on the rehabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…Indeed, given the rising prevalence among the aging population, it is essential to find rehabilitative and preventive strategies for managing sarcopenia that can be carried out outside the hospital environment. 5 , 12 , 29 , 36 Simple exercises, suitable for daily home use, even by patients with limited mobility, appear to contribute to reducing age-associated muscle loss and its consequences. Furthermore, participants showed improvements in both physical and mental well-being, although the increase in physical well-being was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, given the rising prevalence among the aging population, it is essential to find rehabilitative and preventive strategies for managing sarcopenia that can be carried out outside the hospital environment. 5 , 12 , 29 , 36 Simple exercises, suitable for daily home use, even by patients with limited mobility, appear to contribute to reducing age-associated muscle loss and its consequences. Furthermore, participants showed improvements in both physical and mental well-being, although the increase in physical well-being was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 5–11 The consequences of immobility encompass a range of issues including neuromuscular weakening, functional limitations, thromboembolism, and substantial healthcare costs. 11 , 12 Consequently, the management of all these progressive muscle-related impairments demands continuous attention. While pharmaceutical interventions remain a consideration, the potential of physical exercise regimens stands as a promising option.…”
Section: Ethical Publication Statementmentioning
confidence: 99%
“…Among the emerging therapies, extracorporeal shock wave therapy (ESWT) is a non-invasive therapeutic intervention used for musculoskeletal disorders, several inflammatory tendon diseases, or spasticity. 11 The findings suggest that ESWT may be useful in decreasing plantar flexor muscle tone for adults and children affected by lower limb spasticity. 10 , 12-16 There are some trials which had also showed that radial extracorporeal shockwave therapy (rESWT) was more effective on augmenting the ankle passive range of motion (PROM) compared to focal extracorporeal shockwave therapy (fESWT).…”
Section: Ethical Publication Statementmentioning
confidence: 91%
“…Additionally, physical exercise can preserve the ability to perform activities of daily living and functional skills in older adults [ 9 , 10 ]. An evidence-based rehabilitation program should start with a comprehensive assessment of the older adult and include therapeutic physical exercise, as well as other strategies that allow closer and more individualized management of frail patients, including patients with cognitive impairment, and consequently improve their quality of life and functionality [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%